The advertisement call of Dendropsophus tritaeniatus (Bokermann, 1965) (Anura: Hylidae) - Teixeira, Bernardo Franco Da Veiga; Giaretta, Ariovaldo Antonio; Pansonato, André (Zootaxa, 2013)
The Dendropsophus rubicundulus (Reinhardt & Lütken) clade (sensu Faivovich et al. 2005) currently comprises nine species (Martins & Jim 2004). Given that internal relationships of the clade are unknown, we follow the arrangement of Napoli and Caramaschi (1998, 1999a, 1999b), where five species are assigned to a D. tritaeniatus species complex: D. tritaeniatus (Bokermann), D. araguaya (Napoli & Caramaschi), D. cerradensis (Napoli & Caramaschi), D. jimi (Napoli & Caramaschi), and D. rhea (Napoli & Caramaschi). This species complex is always associated to permanent springs and streams in Brazilian Cerrado formations, sharing a small body size, and a dorsal pattern of two anterior brown stripes from the posterior corner of eyes to nearly the middle of body, followed by a single sacral stripe (Napoli & Caramaschi 1999a).